Understanding Climate Change : a practical guide - Spellman, Frank R. (Lanham: Bernan Press, 2021)
"In this thought-provoking title, environmental science author and professor Frank Spellman, PhD, gives a clear-eyed and concise overview of climate change--explaining what is really happening, why it is happening, and what we should do about it"--
Includes bibliographical references and index.
Keywords: Climatic changes; Climate change mitigation